POLA PENDIDIKAN ALTERNATIF BAGI MASYARAKAT NELAYAN DI WONOKERTO KABUPATEN PEKALONGAN - Fihris, Fihris (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2013)
Â This paper is aimed at describing the pattern of education on coastal fishing communities in north coast of Central Java,Â  precisely at the district of Wonokerto-Pekalongan.Â  Theoretically, it attempts to find out the factors of low interest in learning among the northern coastal fishing communities since the crisis in 1998 to the present economic condition that seems more uncertain. As a result, education is an expensive thing and difficult to afford. Therefore, this paper tries to find out suitable solution on the pattern of alternative education for them. This is in accordance with the need of facing the globalization era in which education is a necessity for them to improve their performance and professionalism to meet with the rapid development of technology in order that the community is not left behind and crushed by global competition. To begin with, this paper attempts to look forward to answering how and why the condition of public education is getting worse and what alternative education is appropriate for them so as to improve the level of knowledge and life skills they have.Â ØµÙØ±Øª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø·Ø±Ø§Ø² Ø§ÙØªØ±Ø¨ÙØ© ÙÙ ÙØ¬ØªÙØ¹ Ø§ÙØµÙÙØ§Ø¯ ÙÙ Ø´Ø§Ø·Ø¦ Ø§ÙØ¨ØØ± Ø§ÙØ´ÙØ§ÙÙ Ø¬Ø§ÙØ© Ø§ÙÙØ³Ø·Ù (ÙÙÙÙØ§Ø±ØªÙ ÙÙØ·ÙØ© Ø¨ÙØ§ÙÙÙØ¬Ø§Ù). ÙØØ§ÙÙ Ø§ÙÙØ§ØªØ¨ (ÙØ¸Ø±ÙØ§) Ø§ÙØØµÙÙ Ø¹ÙÙ Ø£Ø³Ø¨Ø§Ø¨ ÙÙØ© Ø±ØºØ¨Ø© Ø§ÙÙØ¬ØªÙØ¹ ÙÙ Ø§ÙØØµÙÙ Ø¹ÙÙ Ø§ÙØªØ±Ø¨ÙØ©Ø ÙÙÙ ÙÙ Ø£Ø²ÙØ© Ø§ÙØªØµØ§Ø¯ÙØ© ÙÙØ° Ø§ÙØ³ÙØ© 1998 Ù ÙØØªÙ Ø§ÙØ¢Ù ÙÙ ØªØªØØ³ÙÙ ØØ§ÙØªÙÙ. Ø£Ø¯Øª ÙØ°Ù Ø§ÙØØ§ÙØ© Ø¥ÙÙ Ø£Ù Ø§ÙØªØ±Ø¨ÙØ© ÙÙ Ø´Ø¦ ØºØ§ÙÂ  Ø¹ÙØ¯ÙÙ ÙØµØ¹Ø¨ Ø§ÙØØµÙÙ Ø¹ÙÙÙØ§Ø Ø«Ù Ø§ÙØ¨ØØ« Ø¹Ù Ø·Ø±Ø§Ø² Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ§Ø®ØªÙØ§Ø±ÙØ© ÙÙÙ. ÙÙÙÙØ§ ÙØ§ÙØª Ø§ÙØ¸Ø±ÙÙØ ÙØ¥Ù Ø§ÙØªØ±Ø¨ÙØ© - ÙÙ Ø¹ØµØ±Ø§ÙØ¹ÙÙÙØ© â Ø´Ø¦ ÙØ§Ø¨Ø¯ ÙÙÙØ§ ÙÙØ¬ØªÙØ¹ Ø§ÙØµÙÙØ§Ø¯ ÙØªØ±ÙÙØ© Ø¬ÙØ¯Ø© Ø¹ÙÙÙÙ ÙÙÙÙÙØªÙÙ ÙØ³Ø§ÙØ±Ø© Ø¨ØªÙØ¯Ù Ø§ÙØªÙÙÙØ©Ø Ø¥Ø°Ø§ Ø£Ø±Ø§Ø¯ÙØ§ Ø£Ù ÙØ§ ÙÙÙÙÙØ§ ÙØ¬ØªÙØ¹Ø§ ÙØªØ®ÙÙÙÙ . Ø¨Ø¯Ø£Øª Ø§ÙÙÙØ§ÙØ© Ø¨Ø§ÙØ¨ØØ« Ø¹Ù Ø§ÙØ¬ÙØ§Ø¨ ÙÙÙÙ ÙÙÙØ§Ø°Ø§ Ø³Ø§Ø¡Øª ØØ§ÙØ© Ø§ÙØªØ±Ø¨ÙØ© ÙÙ ÙØ°Ø§ Ø§ÙÙØ¬ØªÙØ¹Ø ÙØ§ ÙÙ ÙÙØ¹ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙÙØ§Ø³Ø¨Ø© ÙÙÙ ÙØªØªØ±ÙÙÙ ÙØ¹Ø§Ø±ÙÙÙ ÙÙÙØ§Ø±Ø§ØªÙÙ ÙÙ Ø§ÙØÙØ§Ø©.